Modeling the magnetic properties and magnetocaloric effect of La0.7Sr0.3Mn0.9Ti0.1O3 - Yahyaoui, S.
We present a simple analysis based on the molecular field theory and on the Bean-Rodbell model to justify the magnetocaloric effect (MCE) on La0.7Sr0.3Mn0.9Ti0.1O3. The modeling the magnetic properties of the La0.7Sr0.3Mn0.9Ti0.1O3 was investigated. Using the Brillouin function we have determined the mean field exchange parameter lambda and the total angular momentum J of the perovskite. The mean-field equation of state leads the system to second order ferromagnetic (FM)-paramagnetic (PM) phase transition. The expressions describing entropy and its change under the influence of magnetic field have been derived. A large magnetic entropy (-Delta S-M) has been observed in our sample with a peak centered on the Curie temperature (T-C = 210 K). The theoretical calculations are compared with experimental behavior. (C) 2016 Elsevier B.V. All rights reserved.